Inculcating Design Thinking Methodology in the Minds of First Year Engineering Students: A Step Towards Entrepreneurial Thinking - Patil, Pratik A.; Patil, Sachin K.; Kulkarni, Sushma S. (Journal of Engineering Education Transformations, 2025)
Every economy needs entrepreneurs to fill gaps and promote innovative products with the necessary expertise and hard work. An entrepreneurial culture hastens a nation’s overall development because it promotes nurturing a greater number of venture capitalists which eventually boosts nation’s economy. Rajarambapu Institute of Technology (RIT) Rajaramnagar, an Autonomous Institute has adopted choice-based curriculum system (CBCS) in 2017-18 which included Entrepreneurship development (ED) as one of the four tracks with the objective to transform students into entrepreneurs. It was observed that, there is dire need to initiate entrepreneurial thinking course in first year engineering curriculum to acquaint students with problem solving and creative thinking skills, communication skills and teamwork which are very important for an entrepreneur. Hence, the course ‘Creativity, Design Thinking and Entrepreneurial Mindset’ was commenced as an open elective for first year engineering students from the academic year 2018-19. In this paper, course details are presented along with course outcomes and In-Semester evaluation (ISE) plan. Design thinking methodology is illustrated phase wise with help of students’ project case study. Innovative active learning tools and techniques were developed to map the required skills for an entrepreneur. Due to this strategically developed active learning tools, course CO attainment has improved from the year 2018-19 to 2021-22; CO1 has improved by 37.09 %, CO2 increased by 47.54%, CO3 by 40.30 % and CO4 improved by 28.98 %. Moreover, number of prototypes developed by the students were 4 in the year 2018-19, which elevated to 15 (increased by 275 %) in the year 2021-22. Furthermore, there was improvement in final year ED track students of 2021-22 as compared to 2020-21; 25 students entered ED track during the year 2020-21, out of which 6 students (24 % students) converted their ideas into startups, while during the year 2021-22, 28 students opted for ED track, from which 13 (46.4 % students) established their startups. Lastly, ED track mentors survey results are reported for the year 2020-21 and 2021-22, which clearly illustrate that ED track students’ entrepreneurial knowledge and abilities, students’ attitude towards entrepreneurship as a career option and students’ entrepreneurial self-efficacy has improved than the previous years.